EFEKTIVITAS PENERAPAN PAJAK CAPITAL GAIN ATAS PEMINDAHTANGANAN TANAH DALAM MEREDAM SPEKULASI DAN INFLASI HARGA TANAH DI INDONESIA - Loso Judijanto (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
This study aims to analyse the effectiveness of capital gains tax on land transfers in curbing speculation and controlling land price inflation in Indonesia. Land speculation has been one of the main causes of uncontrolled land price increases, thereby disrupting market stability and public access to land ownership. Capital gains tax as a fiscal instrument is expected to curb speculative activities by imposing tax on profits from land sale and purchase transactions. The research method used a literature review with data sources from taxation regulations, government reports, and previous studies in the field of taxation and the property market. The results of the study show that capital gains tax has great potential to reduce land speculation and stabilise land prices, provided that it is supported by well-designed policies, effective administrative management, and a high level of taxpayer compliance. These findings emphasise the importance of synergy between fiscal policy and land governance to achieve a fair and sustainable land market in Indonesia.